In a network of lines that intersect: The socio-economic development impact of marine resource management and conservation in Southeast Asia. (October 2021) - Haenssgen, Marco J.; Savage, Jessica; Yeboah, Godwin; Charoenboon, Nutcha; Srenh, Sorn
Highlights: We study the human dimension and socio-economic impacts of marine protection across selected Southeast Asian countries. Our novel conceptual framework focuses on linkages between marine conservation, communities, human services, and nature. The qualitative case study of a Cambodian fishery demonstrates economic relief but also social exclusion and anxieties. Our innovative exposure assessment linked marine protection to decreasing wealth and increasing child mortality. Marine protection needs to accommodate diverse communities and parallel social policy should support livelihood adaptation. Abstract: Marine protected areas (MPAs) are rapidly spreading to meet global conservation targets, but new governance arrangements can have unintended impacts on socio-economic development that can undermine and counteract their intended outcomes. We use an exploratory mixed-method research design to understand these development impacts and their underlying mechanisms, guided by an innovative activity space framework that situates marine resource management and conservation in a network of relationships between communities, human services, and nature. Qualitative research – based on 22 interviews in Koh Sdach Archipelago, Cambodia – demonstrates how the local community experienced improving relationships with the state and a slowing deterioration of marine resources, but also social division, heightened livelihood anxiety, and potentially a false sense of economic security. We hypothesise on this basis that marine conservation could impede socio-economic development, for which we find support in our quantitative analysis across Cambodia, the Philippines, and Timor-Leste: MPAs materialised in better-off communities but were associated with slower and partly regressive socio-economic development, in particular decreasing wealth and increasing child mortality. These findings suggest that the rapid global expansion of MPA coverage in its current, environmental-conservation-focused form is problematic as it disregards local social realities. Livelihood adaptation support should complement the implementation of marine resource governance mechanisms to mitigate unintended negative consequences.